EVALUATION OF ANTHROPOMETRIC PARAMETERS OF PATIENTS WITH CONGENITAL BULLOUS EPIDERMOLYSIS WITH AN ALLERGIC REACTION - Ikramova Nargiza Alisher qizi; Salimova Sabriniso Mamadali qizi; Rahimjonov Sohibjon Olimjon oʻgʻli; Baxtiyorova Jasmina Botir qizi; Eshpoʻlatova Malikabonu Sherali qizi (Modern American Journals, 2025)
Congenital epidermolysis bullosa (CEB) is a prototype of a group of genodermatoses with skin fragility. CEB is a severe orphan disease characterized by lesions of not only the skin but also the mucous membranes, with the formation of blisters and erosions in response to minimal mechanical stress. Epidemiological data vary worldwide; the prevalence of CEB, according to various sources, ranges from 9.6 to 11.07 per 1,000,000 people.